PENGIRIMAN DATA MENGGUNAKAN NRFT24L01+LA+PA DENGAN JARAK 200M - ajie pangestu; Juni Marwanto; Indra Dwisaputra; Surojo Surojo (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Wireless Sensor Network (WSN) is a wireless network infrastructure that uses sensors to monitor physical or environmental conditions such as temperature, sound, vibration, electromagnetic waves, pressure, movement, and others. In this study, considerations were made in choosing the nrf24l01+LA+PA component, namely how far the data transmission distance was sent. The value measurement uses the mpu-6050 sensor as data sent via nrf24l01+LA+PA. With the accuracy of the values ​​issued by the mpu-6050 sensor. In testing the tool using two scenarios so that there are differences in environmental conditions and the distance traveled.